The Impact of Educator Salary Financing Schemes on Basic and Higher Education Quality in Indonesia - Misbahul Arifin; Diana Khoiriyah (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
This study examines the relationship between educator salary financing policies and the quality of education at both basic and higher levels in Indonesia, with the primary objective of identifying how different salary financing schemes influence teacher welfare, motivation, and ultimately educational outcomes. Using a library research method, this study relies on primary sources such as government regulations and policy documents as well as secondary sources including scholarly articles, reports, and statistical data, with data analyzed through content analysis to explore patterns, comparisons, and critical interpretations. The findings show that educator salary financing plays a decisive role in shaping the overall quality of education, where adequate and sustainable financing schemes improve teacher welfare, performance, classroom engagement, and research productivity, while inadequate or uneven financing structures pose challenges in achieving national education goals. These results suggest that salary financing should be considered not merely as a budgetary expense but as a strategic investment in educational development. The implication of this study is the urgent need for policymakers to design equitable, transparent, and sustainable financing models that align with Indonesia’s long-term vision of improving educational quality.